Tuổi thành tạo của khoáng hóa Molipden Ô Quy Hồ, Tây Bắc Việt Nam và ý nghĩa địa chất - Hiếu, Phạm Trung (Vietnam Journal of Earth Sciences, 2012)
SUMMARY Age of molybdenite mineralization from the O Quy Ho deposit of Northwestern Vietnam and its geological significance The pyrite Rb-Sr technique has been used to determine the timing of mineralization, the results showed that O Quy Hồ molipdenite mineralization of northwestern Vietnam was formed in Paleogene ( c.a 38 Ma). The molydenite mineralization is contemporaneous to the formation of fine-grained porphyric granite and lecogranite of Ye Yen Sun complex. Combined with relevant isotope studies (87Sr/86Sr)i, the data indicate the source of the mineralization are complex and can be supplied from surrounded rock and the Mo deposits in the northwestern Vietnam were related to the India-Asia collision during the Eocene.